Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3390/toxins6071979
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of the Venom of a New Taipan Species, Oxyuranus temporalis, with Other Members of Its Genus

Abstract: Taipans are highly venomous Australo-Papuan elapids. A new species of taipan, the Western Desert Taipan (Oxyuranus temporalis), has been discovered with two specimens housed in captivity at the Adelaide Zoo. This study is the first investigation of O. temporalis venom and seeks to characterise and compare the neurotoxicity, lethality and biochemical properties of O. temporalis venom with other taipan venoms. Analysis of O. temporalis venom using size-exclusion and reverse-phase HPLC indicated a markedly simpli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 33 publications
3
21
0
Order By: Relevance
“…2). This finding confirms that the very rapid neurotoxic activity of O. temporalis venom in chick biventer cervicis physiological assay, reported by Barber et al [39], is due to an extremely high concentration of postsynaptic α-neurotoxins (iBAQ abundance = 97.9%). A recent study sequenced the α-Elapitoxin-Ot1a short-chain αneurotoxin from this species and found it to be a potent and abundant venom constituent [40].…”
Section: Venom Of Mammal-eating Western Desert Taipan Consists Predomsupporting
confidence: 90%
See 1 more Smart Citation
“…2). This finding confirms that the very rapid neurotoxic activity of O. temporalis venom in chick biventer cervicis physiological assay, reported by Barber et al [39], is due to an extremely high concentration of postsynaptic α-neurotoxins (iBAQ abundance = 97.9%). A recent study sequenced the α-Elapitoxin-Ot1a short-chain αneurotoxin from this species and found it to be a potent and abundant venom constituent [40].…”
Section: Venom Of Mammal-eating Western Desert Taipan Consists Predomsupporting
confidence: 90%
“…chains belonging to taipoxin and paradoxin clades ( There is an indication that α-neurotoxin abundance may vary geographically. For example, a more reduced effect of Saibai Island Oxyuranus scutellatus venom on chick biventer cervicis contractile response to acetylcholine suggests that this population would have even lower expression of α-neurotoxins than the specimens from the mainland [39]. O. scutellatus and O. microlepidotus venoms also contained prothrombinase toxins, but less than in some Pseudonaja venoms (Table 1).…”
Section: Other Mammal-eating Taipans Possess Venoms Rich In Pla2 Neurmentioning
confidence: 99%
“…The toxic components often include neurotoxins which assist in the immobilization and capture of prey but also may cause clinical neurotoxicity following systemic envenoming in humans. We have recently studied O. temporalis venom and shown that the reverse-phase HPLC venom profile consists of only a few peaks with the major peak eluting around 15 min [ 4 ]. Previous studies conducted in our laboratory have shown that, under the same reverse-phase HPLC conditions, short-chain postsynaptic neurotoxins elute from the reverse phase column between 15–17 min [ 16 , 17 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…O. temporalis venom was obtained as previously described [ 4 ] from two live specimens of O. temporalis held at the Adelaide Zoo (Adelaide, South Australia, Australia). After extraction, the venom was frozen with dry ice, transferred into a −20 °C freezer and then lyophilized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation